A user-centric approach for developing and deploying service front-ends in the future internet of services. (3rd August 2009) - Lizcano, David; Soriano, Javier; Reyes, Marcos; Hierro, Juan J.
Service-Oriented Architectures (SOAs) based on web services have attracted a great deal of interest and Internet Technology (IT) investment over the last few years, principally in the context of business-to-business integration within corporate intranets. However, they are now evolving and breaking through enterprise boundaries in a revolutionary attempt to make the approach pervasive. This is leading to what we call a user-centric SOA. A user-centric SOA is an SOA conceived as an internet of services made up of compositional resources empowering end users to collaboratively remix and ubiquitously exploit these resources. In this paper we explore the architectural basis, technologies, frameworks and tools considered necessary to tackle this novel vision of SOA. We also present the rationale behind EzWeb/FAST, an ongoing EU-funded project whose first outcomes could serve as a preliminary proof of concept.